X-ray imaging of subsurface dynamics in high-Z materials at the Diamond Light Source - Eakins,D; Chapman,D (Review of Scientific Instruments, 2014)
In this paper, we describe a new approach enabling study of subsurface dynamics in high-Z materials using the unique combination of high-energy synchrotron X-rays, a hybrid bunch structure, and a new dynamic loading platform. We detail the design and operation of the purpose-built, portable small bore gas-gun, which was installed on the I12 high-energy beamline at the Diamond Light Source and used to drive compression waves into solid and porous metal targets. Using a hybrid bunch structure and broadband X-ray pulses of up to 300 keV, radiographic snapshots were captured during various dynamic deformation processes in cm-scale specimens, thereby contributing to a more complete understanding of the evolution of mesoscale damage. Importantly, we highlight strategies for overcoming the challenges associated with using high-energy X-rays, and suggest areas for improvement needed to advance dynamic imaging through large-scale samples of relevance to engineering scenarios. These preliminary measurements demonstrate the feasibility of probing highly transient phenomena using the presented methodology.